Pemodelan Pengukuran Kesiapan untuk Keberhasilan Implementasi Sistem Enterprise Resource Planning - Santo Fernandi Wijaya; Jansen Wiratama; Angelina Ervina Jeanette Egeten (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
In the digital era, companies are required to optimize technological innovation to increase capacity in achieving work that is more efficient, effective, productive, and has a competitive advantage. Companies must use the enterprise resource planning (ERP) system to improve efficiency, effectiveness, and productivity. Implementing an ERP system provides competitive advantages by means of decision-making proven for fast and precise management. ERP system is an integrated information system for strategic company management decision-making. For this reason, implementing an ERP system is necessary. Unfortunately, the fact shows that many companies fail to implement an ERP system, resulting in costly implementation expenses. Previous research has discussed empirical studies on the critical success factors for implementing an ERP system effectively. Therefore, further research still needs to be done by discussing ERP implementation from the perspective of measuring companies’ readiness levels in ERP system implementation. This research methodology criticized and analyzed the comparison of eleven prior research articles as a basis for developing a model to measure companies’ readiness levels in implementing ERP systems. This research examined quantitative data gathered through the use of questionnaire method to rank indicators for measuring companies’ readiness levels by identifying four dimensions and 27 indicators. This research aims to produce a model for measuring companies’ readiness to implement the ERP system on time successfully.